Anmerkungen zur aktuellen Geldpolitik des Eurosystems - Rohde, Armin (Estonian Discussions on Economic Policy, 2014)
In the present article a recently observable very expansive monetary policy not only in the Eurosystem but also in nearly all leading industrialized countries is analysed as a result of a fundamental change in monetary policy strategy. The goal of research is to show that this fundamental change in monetary policy from concentrating on developments of the quantity of money to focusing strictly on developments of interest rates and interest rate levels is the most important reason for recent most expansive monetary policy, which is described best by a strategy of lowest interest rate policy and which deals with interest rate levels of zero or near zero percent. It is argued in the present article too, that a lasting period of very low interest rates is connected with severe dangers or disadvantages not only for special institutions of the companies sector and for private household savings, but also for investments in real capital and for solving debt crises, because it gives wrong economic incentives. In addition such an expansive monetary policy forced investors to look at investments with higher risks, to get a better expected return on investment, which could be the reason for new financial instabilities. At least the outright monetary transactions programme of the ECB is discussed. This OMT-Programme could be seen as a proper monetary policy instrument of the recent interest rate policy strategy, especially to transmit central banks key interest rate changes to all segments of the financial markets in all member countries of the Euro area. But there are very different or even conflicting interpretations of the sense of that programme between ECB and Deutsche Bundesbank. This strong conflict can be discussed as fundamental difference of how monetary policy should act in recent days